2021
DOI: 10.1101/2021.01.22.427763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Succinate Dehydrogenase (SDH)-subunit C regulates muscle oxygen consumption and fatigability in an animal model of pulmonary emphysema

Abstract: Patients with pulmonary emphysema often develop locomotor muscle dysfunction, which is independently associated with disability and higher mortality in that population. Muscle dysfunction entails reduced force-generation capacity which partially depends on fibers’ oxidative potential, yet very little mechanistic research has focused on muscle respiration in pulmonary emphysema. Using a recently established animal model of pulmonary emphysema-driven skeletal muscle dysfunction, we found downregulation of succin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, while downregulation of muscle succinate dehydrogenase (SDH) has been consistently shown in COPD patients [72][73][74], we have recently reported that reduced expression of SDH subunit C (SDH-C) contributes to muscle metabolic dysfunction in IL13 TG mice [48]. SDH dysfunction leads to succinate accumulation [48], which has recently been shown to influence the regulation of cyclin-dependent kinase 2 (CDK2)-driven phosphorylation in satellite cells via succinate receptor SUCNR1 [75]. As CDK2 is a critical regulator of cell division, succinate could articulate metabolic and myogenic dysregulations in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while downregulation of muscle succinate dehydrogenase (SDH) has been consistently shown in COPD patients [72][73][74], we have recently reported that reduced expression of SDH subunit C (SDH-C) contributes to muscle metabolic dysfunction in IL13 TG mice [48]. SDH dysfunction leads to succinate accumulation [48], which has recently been shown to influence the regulation of cyclin-dependent kinase 2 (CDK2)-driven phosphorylation in satellite cells via succinate receptor SUCNR1 [75]. As CDK2 is a critical regulator of cell division, succinate could articulate metabolic and myogenic dysregulations in this context.…”
Section: Discussionmentioning
confidence: 99%
“…At specified days after the second injury procedure, the TA muscles were collected and frozen histologically. Due to the COPD-induced muscle atrophy that is intrinsic to the animal model [43,44,47,48], we scored the fibers cross sectional area after full reconstitution of histological integrity, in the left TA muscle, as a percentage of the expected value, which is the CSA of the right (saline-injected) TA muscle.…”
Section: Induction Of Muscle Injurymentioning
confidence: 99%